Using satellites to make Flood Index Insurance scalable and helping farmers survive floods in India and Bangladesh - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
IBFI products tested to thousands more farmers through private sector partnerships. In India, its work with WRMS will help to insure 25,000 farmers against floods and other risks, and in Bangladesh, a partnership with Green Delta Insurance Company is making the insurance available to 100,000 farmers.